2023
DOI: 10.4081/jphia.2023.2323
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological profile associated with lifestyle risk factors and nutritional status for COVID-19 patients in the Iraqi population

Abstract: Objectives. To determine the prevalence of covide19 infection and to identify the lifestyle factors and nutritional status associated with the epidemiological profile of covid19 patients. Methods. This cross-sectional survey was carried out in the eighteen Iraqi governorates, from 1st August to 20th of October 2020. At the end of this study, 433 participants were recruited . Results. The prevalence of coronavirus infection was 37.18%. Smoking and Active physical activity were relatively higher for covid19 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Several risk factors have been recognized to affect COVID-19 infection, such as socioeconomic, anthropometric, and lifestyle factors [10]. Several studies have demonstrated that health outcomes like the probability of developing a disease and then dying are highly associated with the socioeconomical state [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors have been recognized to affect COVID-19 infection, such as socioeconomic, anthropometric, and lifestyle factors [10]. Several studies have demonstrated that health outcomes like the probability of developing a disease and then dying are highly associated with the socioeconomical state [11].…”
Section: Introductionmentioning
confidence: 99%